On sufficient statistics for optimal stopping problems of stochastic processes - Grigelionis, B. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Б. И. Григелионис. К вопросу о достаточных статистиках для задач об оптимальной остановке случайных процессов B. Grigelionis. Pakankamų statistikų atsitiktinių procesų optimalaus sustabdymo uždaviniams klausimu